Urban consolidation center or peer-to-peer platform? The solution to urban last-mile delivery - DENG, Qiyuan (Institutional Knowledge at Singapore Management University, 2019)
Booming e-commerce activities further increase this demand, exerting intense pressure on the cities' well-being. To build a city with congestion and pollution under control, a consolidator can operate an urban consolidation center (UCC) to bundle shipments from multiple carriers before the last-mile delivery. Alternatively, the consolidator can operate a peer-to-peer platform for the carriers to share their delivery capacity. Our objective is to compare the performance of these two business models. Under each business model, we study the interactions between a consolidator and multiple carriers using a two-period game-theoretical model. In each period, the consolidator first chooses a delivery fee to maximize her expected profit. Each carrier then observes his task volume, and decides whether to deliver on his own or use the consolidator's service to minimize his expected cost. Under the UCC model, the carriers become more dependent on the UCC to deliver their tasks as their variable delivery cost increases or their logistics reestablishment cost decreases. Under the platform model, the carriers generally keep their logistics capability (even if they purchase capacity from the platform) in equilibrium to ensure their flexibility of selling capacity on the platform. Between the two business models, it is generally more profitable for the consolidator to operate the UCC than the platform if the carriers' fixed delivery cost is large. Furthermore, the UCC becomes more dominant as there are more carriers. If the number of carriers is large, it is also more efficient for the consolidator to operate the UCC than the platform to reduce the expected social-environmental cost. Otherwise, the platform is more efficient.